Communication between healthcare professionals and relatives of patients approaching the end-of-life: A systematic review of qualitative evidence. (September 2019) - Anderson, Rebecca J; Bloch, Steven; Armstrong, Megan; Stone, Patrick C; Low, Joseph TS
Background: Effective communication between healthcare professionals and relatives of patients approaching the end-of-life is vital to ensure patients have a 'good death'. To improve communication, it is important to first identify how this is currently being accomplished. Aim: To review qualitative evidence concerning characteristics of communication about prognosis and end-of-life care between healthcare professionals and relatives of patients approaching the end-of-life. Design: Qualitative systematic review (PROSPERO registration CRD42017065560) using thematic synthesis. Peer-reviewed, English language articles exploring the content of conversations and how participants communicated were included. No date restrictions were applied. Quality of included studies was appraised using the Joanna Briggs Institute Critical Appraisal Checklist for Qualitative Research. Data sources: An electronic database search of CINAHL, MEDLINE, PsycINFO and EMBASE was performed. Results: Thirty-one papers were included. Seven themes were identified: highlighting deterioration; involvement in decision-making, post-decision interactional work, tailoring, honesty and clarity, specific techniques for information delivery and roles of different healthcare professionals. Varied levels of family involvement in decision-making were reported. Healthcare professionals used strategies to aid understanding and collaborative decision-making, such as highlighting the patient's deterioration, referring to patient wishes and tailoring information delivery. Doctors were regarded as responsible for discussing prognosis and decision-making, and nurses for providing individualized care. Conclusion: Findings suggest training could provide healthcare professionals with these strategies to improve communication. Interventions such as question prompt lists could help relatives overcome barriers to involvement in decision-making. Further research is needed to understand communication with relatives in different settings and with different healthcare professionals.